EMPLOYEE TURNOVER INTENTION AND SUPPLY CHAIN MANAGEMENT FOR VALUE CREATION IN INDONESIAN BANKS - Irawan, Yanuar; Bangsawan, Satria; MS, Mahrinasari (International Journal of Supply Chain Management, 2020)
The primary objective of this study is to examine the psychological role of customer behavior on turnover intention. Moreover, this study examined the mediating role of employee behavior and employee performance. After collecting primary data from Indonesian banks, the relationship between customer behavior, employee behavior, performance and turnover intention was examined. 180 valid questionnaires were returned and used for data analysis. Results of the study highlighted that customer behavior has significant psychological effect on turnover intention. It is found that positive customer behavior leads to the positive employee behavior. However, negative customer behavior with employee effect negatively on employees of banks. Further, employee behavior influence employee performance and turnover intention. Therefore, customer behavior has direct and indirect effect on employee turnover intention among banks. Hence, this study has significant contribution to the literature by examining the relationship between customer behavior, employee behavior, performance and turnover intention. Practically, this study is much beneficial for banking industry to overcome the crucial issue of employee turnover intention. Besides, our study has provided an addition to empirical evidences while testing the direct impact of supply chain management on value creation. It is found that two out of three factors of supply chain (order process management, information technology management) are directly impacting on the value creation in the banking sector of Indonesia.